Intelligent hydraulic fracturing under industry 4.0—a survey and future directions - Jing Jia; Qinghu Fan; Jianglu Jing; Kehui Lei; Lichang Wang (Journal of Petroleum Exploration and Production Technology)
Abstract This paper investigates the automation of hydraulic fracturing within the context of Industry 4.0, defining intelligent fracturing systems through three components: surface equipment, downhole sensing, and software control systems. The study addresses major advancements such as real-time optimization of fracturing parameters, intelligent allocation of fracturing fluids and materials, risk early warning systems, and fracture monitoring. It identifies four technical challenges: integrating heterogeneous data, developing intelligent decision-making algorithms, adaptive surface equipment adjustments, and multi-machine collaborative control. The paper reviews technological progress, foresees future benchmarks, and predicts the potential for unmanned fracturing operations, including site reconnaissance, autonomous fracturing unit driving, intelligent wellsite layout, fluid mixing, and operation execution. This comprehensive review delineates the developmental framework of intelligent fracturing, outlines key challenges, and forecasts future trends, marking a significant contribution to the field.